In vitro antimicrobial activity of selected essential oils against bacteria and yeasts isolated from the genital tract of mares. Issue 10 (23rd May 2022) - Ebani, Valentina Virginia; Nardoni, Simona; Bertelloni, Fabrizio; Pollera, Claudia; Pistelli, Luisa; Mancianti, Francesca
Abstract: The aim of the present study, the first to test clinical equine isolates, was to evaluate the antimicrobial activity of commercial essential oils (EOs) obtained from Origanum vulgare, Thymus vulgaris, Cinnamomum zeylanicum, Cymbopogon citratus, Aloysia triphylla and Syzygium aromaticum against Streptococcus spp., Staphylococcus spp., Candida albicans and Rhodotorula spp. previously isolated from uteri of mares with reproductive disorders. T. vulgaris showed the best antibacterial activity against all the selected agents, with MICs ranging from 0.07 mg/mL for S. equi subsp. zooepidemicus to 0.29 mg/mL versus Streptococcus sp. and Staphylococcus spp. isolates and versus C. albicans and Rhodotorula spp., with MICs of 0.46 mg/mL and 1.86 mg/mL, respectively. O. vulgare, S. aromaticum, C. zeylanicum EOs showed good antibacterial activity with MICs ranging from 0.07 mg/mL to 0.29 mg/mL, 0.16 mg/mL to 0.32 mg/mL, 0.07 mg/mL to 0.63 mg/mL, respectively; A. triphylla was the most active EO against Rhodotorula spp. (0.43 mg/mL). Graphical Abstract: UF0001